2009
DOI: 10.1016/j.bbrc.2009.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Targeted connexin26 ablation arrests postnatal development of the organ of Corti

Abstract: Mutations in the gene coding for connexin26 (Cx26) is the most common cause of human nonsyndromic hereditary deafness. To investigate deafness mechanisms underlying Cx26 null mutations, we generated three independent lines of conditional Cx26 null mice. Cell differentiation and gross cochlear morphology at birth seemed normal. However, postnatal development of the organ of Corti was stalled as the tunnel of Corti and the Nuel's space were never opened. Cell degeneration was first observed in the Claudius cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
155
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 99 publications
(169 citation statements)
references
References 19 publications
12
155
1
Order By: Relevance
“…In addition, the tunnel of Corti and spaces of Nuel never opened. These results demonstrate that connexin26 plays a role in the postnatal maturation and survival of cells in the organ of Corti Wang et al 2009). The second ROSA26-CreER TM allele (Badea et al 2003) was used to delete Kif3a, a ciliary protein, at E10.5.…”
Section: Cre/creer Lines With Ubiquitous Expressionmentioning
confidence: 57%
See 1 more Smart Citation
“…In addition, the tunnel of Corti and spaces of Nuel never opened. These results demonstrate that connexin26 plays a role in the postnatal maturation and survival of cells in the organ of Corti Wang et al 2009). The second ROSA26-CreER TM allele (Badea et al 2003) was used to delete Kif3a, a ciliary protein, at E10.5.…”
Section: Cre/creer Lines With Ubiquitous Expressionmentioning
confidence: 57%
“…By E13.5, reporter expression was found throughout the otic lines are used. The most commonly used line is the depending on the strength of the fluorescent reporter COX ET.AL: Conditional Gene Expression in the Mouse Inner Ear Using Cre-loxP Pirvola et al 2002;Arnold et al 2006;Zelarayan et al 2007;Barrionuevo et al 2008;Jones et al 2008;Rickheit et al 2008;Grimsley-Myers et al 2009;Schultz et al 2009;Wang et al 2009;Yamamoto et al 2009;Deng et al 2010;Freyer and Morrow 2010;Haugas et al 2010;Hurd et al 2010;Hwang et al 2010;Sipe and Lu 2011 (Hebert and McConnell 2000), which has been reported to cause haploinsufficiency phenotypes that include proliferation in other organs (Shen et al 2006;Eagleson et al 2007;Siegenthaler et al 2008). However, no change in proliferation in the inner ear has been reported in several papers where proper controls of Foxg1-Cre mice (without the floxed allele) were used (Yamamoto et al 2009(Yamamoto et al , 2011Hartman et al 2010;Brown and Epstein 2011).…”
Section: Cre/creer Lines For the Developing Otic Vesicle And Otocystmentioning
confidence: 99%
“…Gap junctions between the cells in these two networks provide a route whereby K + passes through the electrochemical gradient for return to the intrastrial space. Secondly, targeted Cx26 ablation leads to the arresting of postnatal development of the organ of Corti and the degeneration of the outer hair cells and the supporting Deiters cells in the conditional Cx26 null mice [40,41]. Lastly, mutations in GJB2 are associated with both dominant and recessive, in either syndromic or nonsyndromic forms, hearing loss [31,42].…”
Section: Discussionmentioning
confidence: 97%
“…Early establishment of the cochlear GJ network may facilitate cochlear development by helping the transport of signal and nutrient molecules in the avascular sensory epithelium of the cochlea. Cellular degeneration in the sensory epithelia, which starts after the onset of hearing at P13, is another common morphological finding in the cochlea of conditional Cx26 (cCx26) null mice (Cohen-Salmon et al, 2004;Wang et al, 2009). We (Sun et al, 2009;Wang et al, 2009) and others (Inoshita et al, 2008) have published data showing that a failure in opening the tunnel of Corti is a hallmark in the developing cochlea of cCx26 null mice.…”
Section: Introductionmentioning
confidence: 93%